Tamsulosin combined with solifenacin versus tamsulosin monotherapy for male lower urinary tract symptoms: a meta-analysis. (2nd September 2015) - Gong, Mancheng; Dong, Wenjing; Huang, Guiying; Gong, Zhaoyang; Deng, Decheng; Qiu, Shaopeng; Yuan, Runqiang
Abstract: Objective: To evaluate the efficacy and safety of tamsulosin and solifenacin combination therapy compared with tamsulosin monotherapy for male lower urinary tract symptoms (LUTS). Methods: We identified all eligible studies that compared tamsulosin and solifenacin combination therapy with tamsulosin monotherapy for male LUTS (up to January 2015). The fixed- or random-effects model was selected depending on the proportion of heterogeneity. Results: Seven articles were identified as eligible for this meta-analysis, with a total of 3063 participants. Synthetic data showed combination therapy had significant improvements in Storage International Prostate Symptom Score (WMD = −0.60; 95% CI: −0.81 to −0.38, P < 0.0001), quality of life (WMD = −0.23; 95% CI: −0.34 to −0.11, P < 0.0001), micturitions per 24 hours (WMD = −0.70; 95% CI: −0.86 to −0.55, P < 0.0001) and urgency episodes per 24 hours (WMD = −0.26; 95% CI: −0.48 to −0.05, P = 0.018). The incidence of adverse effects in the tamsulosin and solifenacin combined therapy group (30.82%) was similar to the tamsulosin monotherapy group (25.75%). Acute urinary retention was seldom reported in the studies and no clinically significant changes regarding Qmax were showed in our meta-analysis. Conclusions: Tamsulosin and solifenacin combination therapy may be a reasonable option for male LUTS patients, especially for those who have significant storage symptoms. However, PVR should be measured during treatment to assess the increase in PVR or the incidence of AUR.